Pengelolaan DAS Kota Padang Berbasiskan Sistem Informasi Geografis - Era Alfansyuri -; Indra Farni - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Changes in soil physical and socio-economic life of the people Padang City be the cause of a decrease the condition of the watershed (DAS). Catchment area management can be done through an assessment of the components of a watershed both spatial and attribute in a system that is comprehensive and and done with integrated management. Preparation of physical watershed data done by utilizing the technology of Geographic Information Systems (GIS) in which GIS has the ability to perform the presentation of data DAS and spatial analyzes to look at the ability of the DAS.